Buckling Behaviour analysis of composite pipes under pure axial compressive loading using ANSYS Software - Jalaluddin, Izzat Imran (IRC, 2018)

(untitled)
Composite materials are the combination of two or more constituents with different properties combined to produce different mechanical properties. Throughout the years, the demand for the composite materials has increased rapidly due to its excellent mechanical properties such as strength, low density, corrosion resisted, enhanced fatigue strength and cost reducing factor. Apart from it, proper fiber orientation of the reinforcement, ply stacking sequence of the composite laminate, and layer thickness of the reinforcement will strengthen the composite material. Buckling phenomena is a critical issue nowadays and it can happen before the failure of the material due to stress. The aim of this study is to investigate on the critical buckling loads of the glass fiber reinforced epoxy pipes and glass-carbon reinforced epoxy pipes with the effect of fiber orientations, varying diameter over thickness ratio, and ply-stacking sequence. 8 layers of glass/epoxy with different fiber orientations was studied for critical buckling load subjected to axial compression loading using linear finite element analysis (FEA). The following orientations were considered: [+55,-55, +55,- 55]°s, [90, ±55, 90]°s, [90, ±55, 0]°s, [0, ±55, 90]°s, [+45,-45, +45, -45]°sand [+65,-65, +65, -65]°s.